Проблемні питання удосконалення правових та процесуальних гарантій прав потрпілих на стадії досудового розслідування - Мартовицька, О. В.; Martovytska, O. V.; Олена Мартовицька (Вісник Луганського держаного університету внутрішніх справ ім. Е. О. Дідоренка. – 2018. – № 4 (84). – С. 123-133, 2018)
У статті розглянуто основні тенденції наукового дослідження з питань правових і процесуальних гарантій прав потерпілих на стадії досудового розслідування. З’ясовано, що незважаючи на певну кількість новел, запроваджених у КПК України 2012 року з удосконалення захисту прав окремих учасників кримінального провадження, є невирішеними проблемні питання, зокрема стосовно захисту прав потерпілого в кримінальному провадженні.

The main tendencies and the state of the scientific research on the issues of legislative consolidation and implementation in investigative and judicial practice of legal and procedural rights guarantees of the victims at the pre-trial investigation stage are considered. The latest publications, studies, various scientific beliefs as well as problematic and controversial directions in the context of the research are analyzed. A comparative analysis of the provisions of the previous and current criminal procedural legislation of Ukraine in order to identify a positive experience in law enforcement and its usage for further improvement, the formulation of conceptual provisions for both theoretical and applied research objectives of the criminal process problematic issues, is carried out. The novelties and additions to the provisions, that were enshrined in the Criminal Procedure Code of Ukraine in 2012, have been investigated resulting in the conclusion that despite their above specified number, including the ones on improving the protection of the individual rights in criminal proceedings, problematic issues regarding the protection of the rights, freedoms and legitimate interests of the victim in criminal proceedings remained unsolved. Based on this, the study was carried out and an assessment of specific shortcomings, gaps and inconsistencies in the provisions of the current criminal procedural legislation of Ukraine have been made. As a result, specific proposals and recommendations on its improvement are provided in terms of ensuring and implementing the protection of the rights, freedoms and legal interests at the pre-trial investigation stage, as well as of other participants in criminal proceedings, whose interests adjoin in the criminal process. It is concluded that such changes will increase the effectiveness of the overall pre-trial investigation and trial, the adoption of legal decisions and ensure the rights of all participants in the criminal process especially the victims. All mentioned aspects are reflected in the study.

Рассмотрены основные тенденции научного исследования по вопросам правовых и процессуальных гарантий прав потерпевших на стадии досудебного расследования. Установлено, что несмотря на определенное количество новелл, которые закреплены в УПК Украины 2012 года относительно усовершенствования защиты прав отдельных участников уголовного производства, остались нерешенными проблемные вопросы, в том числе по защите прав потерпевшего в уголовном производстве.
Problematic Aspects of Legal and Procedural Guarantee Improvement of the of Victims’ Rights at the Stage of Pre-trial Investigation
Проблемные вопросы усовершенствования правовых и процессуальных гарантий прав потерпевших на стадии досудебного расследования
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; досудове розслідування; кримінальне провадження; захист прав потерпілого; потерпілий; удосконалення законодавства; досудебное расследование; pre-trial investigation; уголовное производство; criminal proceedings; защита прав потерпевшего; потерпевший; усовершенствование законодательства; perfection of legislation